2015
DOI: 10.3399/bjgp15x686113
|View full text |Cite
|
Sign up to set email alerts
|

Statin prescribing for primary prevention of cardiovascular disease: a cross-sectional, observational study

Abstract: BackgroundThe updated (2014) National Institute for Health and Care Excellence (NICE) guideline lowered the recommended threshold for statin prescription from 20% to 10% 10-year cardiovascular disease (CVD) risk. AimTo determine the characteristics of patients prescribed statins for primary prevention according to their CVD risk. Design and settingCross-sectional study in primary care settings in the three east London CCGs (Newham, City and Hackney, and Tower Hamlets). MethodData were extracted from electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 13 publications
3
21
1
3
Order By: Relevance
“…Of these, 151 788 had a recorded CVD risk score since 2012 (10.67%) and 217 860 were initiated on a statin (15.31%). Among patients initiated on a statin after 2012, 27.1% had a documented QRISK2 score: 2.7% of low-risk, 13…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 151 788 had a recorded CVD risk score since 2012 (10.67%) and 217 860 were initiated on a statin (15.31%). Among patients initiated on a statin after 2012, 27.1% had a documented QRISK2 score: 2.7% of low-risk, 13…”
Section: Resultsmentioning
confidence: 99%
“…Relationship between QRISK2 scoring and statin initiation. QRISK2 scores were categorised into low (<10%), intermediate (10)(11)(12)(13)(14)(15)(16)(17)(18)(19).9%) and high (>20%) 10-year CVD risk. In each category, the proportion of patients initiated on statins following QRISK2 scoring was established based on the patient's latest record.…”
Section: Secondary Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] In the context of primary prevention, there is evidence both of undertreatment of high-risk patients (above the treatment threshold) and inappropriate treatment of low-risk patients (below the treatment threshold). [21][22][23][24] Moreover, patients with the highest absolute CVD risk are at greatest risk of being undertreated. 25 One reason for this is that risk scores may not be consistently used by clinicians to guide decision-making.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Although controlled clinical studies proved the efficacy of primary prevention with statins in reducing all-cause mortality and the risk of primary cardiovascular events [30,31], other observational studies also reported the undertreatment of patients eligible for preventive lipid-lowering therapy [27,[32][33][34][35][36]. The rates of undertreatment with antihypertensive agents are lower [36][37][38], which can be explained by well-established evidence on efficacy, good safety profiles and the low cost of these drugs [37].…”
Section: Discussionmentioning
confidence: 99%